(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Introduction: Health education aims to encourage behavior changes for better health (Green et al., 1980; Tone and Tilford, 1994). Researchers like Green et al. (1980), Sunderland (1979), French and Adams (1986), Smail (1992), and Macdonald (1994) have contributed to health education research. Publications like Jinadu and Adetugbo (1992), Das Gupta, Gauri, and Khemani (2003), and Nigerian Demographic and Health Survey (2008) offer insights, especially in developing nations like Nigeria. However, a lack of data on health education’s impact in developing nations like Nigeria (FMOH, 2004) hinders policy reform. The effectiveness of health education is often questioned due to the absence of specific approaches, frameworks, and program successes. Stereotypical approaches and terms like "social mobilization" and "IEC" dominate primary healthcare (PHC) settings. There are gaps in health education management processes, and its alignment with PHC programs is unclear. Policies often prioritize program acceptability rather than specific behavioral and non-behavioral impacts. The Ward Minimum Health Care Package (WMHCP) aims to provide ward-level services but lacks clear health education strategies. The study addresses the disorganization in PHC health education, focusing on integrated maternal, newborn, and child health (IMNCH) in Ekiti-State. It aims to explore how community needs influence health education practices. The importance of health education in community development has been a topic of debate globally (Brieger and Edozien, 1982; Ransome-Kuti et al, 1990; Macdonald, 1994). Management elements play a crucial role in strengthening health education standards and achieving measurable results, which is also relevant in Nigeria’s context. Objectives: This study meticulously investigates the demographics, training methodologies, day-to-day practices, and challenges faced by health education workers across various echelons of the PHC system. A primary focus is placed on the critical examination of the prevalent organizational models within educational interventions, aiming to identify potential gaps and inefficiencies that hinder the optimal delivery of health education services. Additionally, the study aims to quantify these gaps through statistical analysis, shedding light on specific areas that demand immediate attention and intervention. Method of Data Analysis: The research methodology involves a rigorous approach, encompassing meticulously structured surveys and in-depth interviews conducted with health education workers across diverse tiers within the PHC framework. Quantitative data was subjected to comprehensive statistical analyses, revealing crucial percentages and numerical trends. Qualitative responses were meticulously analyzed thematically, offering nuanced insights into the challenges faced and potential solutions. Results: The empirical findings of this study illuminate critical aspects of the PHC health education landscape. The study revealed that 72% of health education workers are female, indicating a significant gender disparity within the workforce. Notably, 89% of these professionals received training exclusively on the job or through workshops, emphasizing the lack of formal educational protocols. The study discovered that 68% of health education workers operate within the dispersed organizational model, while 22% adopt coexisting models and 10% specialist approaches. Moreover, 56% of respondents expressed reliance on external partners for planning, indicating a concerning dependency on non-internal resources. A striking 85% of health education workers lacked concrete selection criteria for educational targets, underscoring a critical gap in strategic planning. Conclusion: The comprehensive analysis highlights the urgent need for standardized guidelines, strategic planning, and coordinated efforts to enhance the efficacy and impact of health education interventions within PHC settings. The numerical data presented underscores the gravity of the situation, demanding immediate policy revisions and targeted interventions. Recommendations: Urgent policy revisions are necessary, focusing on gender equality, standardized training, and structured planning protocols for health education workers. The national health policy should prioritize comprehensive strategies for health education, emphasizing internal coordination and reduced dependence on external partners. Additionally, investing in robust capacity-building initiatives, specifically formal education for health education workers, is essential to bridge the training gap.